Developers’ Data Protection in the Open-Source Application with the Copyleft License - Serfiyani, Citi Rahmati; Yustisia Serfiyani, Cita; Hariyani, Iswi; Tharifah Arsari, Devina (University of Jember, 2021)
Copyright protection of digital products in an open-source system has led to the emergence of copyleft against copyright. Copyleft licenses in open-source serve to impose limits on creations to protect creators' moral rights. At the same time, personal data protection is one part of personal rights amidst the advent of information technology. The development of copyleft products and licenses that usually take place online can potentially lead to violations that harm application developers’ personal data. This paper aimed to characterize copyleft as an antithesis of copyright and analyze legal protection on the open-source application developers' personal data. Using legal research, this paper showed that open-source licenses could consist of two categories. First, non-copyleft licenses in the form of permissive licenses, included in the software under it and are subject to copyright. Second, the copyleft license, which required licenses to modify and distribute copyleft products. This open-source license adopted a form of a standard contract and personal data protection in copyleft products through open-source sites were using a preventive and repressive way. This paper recommended a copyleft-based legal protection mechanism and creators' data by considering the comparative aspects of the copyleft and copyright concepts' characteristics to respect moral rights. KEYWORDS: Personal Data Protection, Indonesia’s Copyright Law, Copyleft License.